Messinian evaporites and fluid flow. (September 2015) - Bertoni, Claudia; Cartwright, Joe
Abstract: Thick evaporite sequences deposited in saline giant basins are traditionally viewed as impermeable barriers to fluid flow. This paradigm has recently been challenged by documented evidence of fluid migration pathways through several-km thick series of evaporites, such as the late Miocene (Messinian) sediments in the Mediterranean basin, deposited during the Messinian Salinity Crisis (MSC). Our paper reviews the occurrence of fluid expulsion events in these evaporites in the depocentres of the basin, and analyses their potential as seal-bypass systems. The Messinian salt giant was deposited in peculiar conditions where massive sea-level changes occurred in a relatively limited time interval, and a thick basin-centre evaporitic series was deposited between pre-MSC and post-MSC deep-water sediments. Consequently, rapid water and sediment loading/unloading events contributed to the creation of overpressures up to fracture and possibly lithostatic gradient, causing the fluids to be released in explosive events. Examples of fluid expulsion events are here grouped and classified in relation to the long and short term effects of the Messinian Salinity Crisis, as well as the local controls and pre-conditioning basin factors. While peaks of fluid expulsion activity during the short time-frame of the MSC can be mainly linked to Mediterranean-wide events, local controls appear to play a major role in post-MSC fluid mobilisation. In these cases, evaporite breach is largely dependent on the availability of pre-MSC undersaturated fluid sources and the capability of the pre-MSC sediments to be overpressured. The analysis here presented can be used as a basis to understand the controls on syn- and post-depositional movement of fluids in sedimentary basins. Moreover, the analysis of temporal and spatial distribution of fluid expulsion events can help define hydrocarbon migration style and pathways in deep-seated petroleum plays. Highlights: We review evidence of fluid migration through tabular Messinian evaporites. We group fluid expulsion events into syn- and post-Messinian Salinity Crisis (MSC). Syn-MSC events are influenced by rapid water and sediment loading/unloading. Post-MSC events are largely controlled by dissolution and overpressure generation. This analysis helps understand evaporite seal breach and petroleum migration style.